Bacteriocin-like substances production by Streptococcus-salivarius against oral bacteria - FANTINATO, V; Zelante, F. (Soc Brasileira Microbiologia, 1991)
Samples of tongue and bucal mucosa surfaces were obtained from six healthy subjects with the purpose of isolating S. salivarius. It was verified that 47 out of 48 S. salivarius strains produced bacteriocin-like substances against at least one of the indicator species: Actinomyces viscosus, Rothia dentocariosa, Streptococcus pyogenes, Staphylococcus aureus, Streptococcus mutans and Streptococcus sanguis. The method employed to test for bacteriocin production was that of deferred antagonism. The results showed that there was a high antagonism against R. dentocariosa, S. pyogenes and A. viscosus; extremely low against S. mutans and S. sanguis and no inhibition for S. aureus.
Keywords: STREPTOCOCCUS-SALIVARIUS; BACTERIOCIN